Ἐκπύρωσις – ZOGNIENIE WSZECHŚWIATA W FILOZOFII STOICKIEJ - Osiński, Piotr (Studia Europaea Gnesnensia, 2017)
This paper is devoted to the Stoic concept of ἐκπύρωσις – the conflagration of universe, its development, its position in the Stoic physical system and related ideas such as ἀποκατάστασις (the reconstruction of universe) as well as the Stoic idea of deity. Also, it addresses the issue of mythological and philosophical sources of the concept in question and presents several examples of its influence.